A meta-analysis with systematic review: Efficacy and safety of immune checkpoint inhibitors in patients with advanced gastric cancer - El Helali, Aya; Tao, Jun; Wong, Charlene H. L.; Chan, Wendy Wing-Lok; Mok, Ka-Chun; Wu, Wing Fong; Shitara, Kohei; Mohler, Markus; Boku, Narikazu; Pang, Herbert; Lam, Ka On (Frontiers in Oncology, 2022)
Background While the efficacy of immune checkpoint inhibitors (ICIs) is increasingly recognized in advanced gastric cancer (aGC), overall survival (OS) has not been consistently improved across the different randomized controlled trials (RCTs). This meta-analysis aimed to quantify the efficacy and safety of ICI and explore potential predictive tumor tissue biomarkers in aGC. Methods A random-effect pairwise meta-analysis was used to evaluate the primary outcome of OS. Sensitivity analysis was performed to investigate the effects of ICIs on PD-L1 status, TMB, MSI-H, and the Asian patient population. We extracted the OS Kaplan–Meier curves from the included trials to compare the effect of PD-L1 status on response to ICIs using DigitizeIt 2.5 and Guyot’s algorithm. Results A pairwise meta-analysis of seven RCTs included in this study showed that ICIs were more effective than the comparator in improving OS (pooled HR: 0.84). We demonstrated that PD-1 ICIs were additive when combined with the comparator arm (pooled HR: 0.79). A sensitivity analysis showed that PD-1 ICIs were associated with better OS outcomes in the Asian patient population as monotherapy (pooled HR: 0.66) or in combination with chemotherapy (pooled HR: 0.83). We demonstrated that tumors with PD-L1 ≥1 (P = 0.02) and PD-L1 ≥10 (P = 0.006) derived OS benefit from ICI monotherapy. Equally, MSI-H (P <0.00001) and TMB-high (P <0.0001) tumors derived favorable survival benefits from ICIs. Conclusions and relevance The results of this meta-analysis suggest that ICIs result in improved OS outcomes in aGC. The benefits varied with different ethnicities, class of ICI, PD-L1 expression, MSI status, and TMB Systematic Review Registration https://www.crd.york.ac.uk/prospero, identifier (CRD42019137829).